2017
DOI: 10.20396/td.v13i1.8648624
|View full text |Cite
|
Sign up to set email alerts
|

Assinaturas tafonômicas em moluscos recentes e seu significado paleoambiental

Abstract: A partir do tipo de dano (injúria) presente nos restos bioclásticos é possível inferir os processos de alteração de informação biológica que agem durante a incorporação destes restos no registro fossilífero. Tais danos, denominadas assinaturas tafonômicas, possuem direta relação com os fatores ambientais que atuaram após a morte e durante a permanência dos bioclastos no sedimento antes da fossilização final, e durante a eodiagênese. Assim, é possível interpretar as condições ambientais a partir da identificaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 130 publications
(221 reference statements)
0
4
0
1
Order By: Relevance
“…A aquisição e descrição dessas assinaturas teve como base Kidwell et al (1986), Davies et al (1988), Best e Kidwell (2000a, b), Simões e Ghilardi 2000e Kidwell et al (2001). O método empregado foi adaptado a partir de análises tafonômicas aplicadas em conchas de depósitos paleolagunares análogos aos estudados aqui (Erthal, 2012;Ritter et al, 2013;Pereira, 2016). Figura 36.…”
Section: Análise Tafonômicaunclassified
“…A aquisição e descrição dessas assinaturas teve como base Kidwell et al (1986), Davies et al (1988), Best e Kidwell (2000a, b), Simões e Ghilardi 2000e Kidwell et al (2001). O método empregado foi adaptado a partir de análises tafonômicas aplicadas em conchas de depósitos paleolagunares análogos aos estudados aqui (Erthal, 2012;Ritter et al, 2013;Pereira, 2016). Figura 36.…”
Section: Análise Tafonômicaunclassified
“…The shells include from complete to fragmented and highly abraded specimens exhibiting varied colors ranging from white, yellow, reddish, and dark gray or black (Fig. 5A), and may show encrustation by barnacles, bryozoans and polychaetes, besides traces of bioerosion by invertebrate predators and parasites (Lopes and Buchmann 2008;Erthal 2012;Lopes 2012;Ritter et al 2019). Other fossils of marine invertebrate species include echinoderms (Fig.…”
Section: The Fossil Assemblages Of the Shelf And Concheirosmentioning
confidence: 99%
“…Shells from these relict deposits initially yielded 14 C ages ranging from 14,580 years BP to more than 30,000 years BP (Figueiredo 1975, fide Erthal 2012). AMS 14 C dates (Ritter et al 2017) of the shallower deposits showed that 97% of the shells were younger than 6,000 years (median=1215 years).…”
Section: Geographical and Geological Settingmentioning
confidence: 99%
“…They found that discoloration correlated with postmortem age. Erthal (2012) and Ritter et al (2017Ritter et al ( , 2019 incorporated color, among other taphonomic attributes, as evidence of diagenesis on the Brazilian shelf. Erthal (2012) found a correlation between light colors (white, cream) and the presence of mud, and more loosely, between reddish colors and deposits abundant in heavy minerals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation